Discovering the antecedents of engagement for citizen centric public service excellence / Norazlin Mohd Nor...[et al.] - Mohd Nor, Norazlin; Tuan Ismail, Tuan Nooraini; Puteh, Fadilah (Universiti Teknologi MARA, Kedah, 2017)
The Malaysian public sector is undergoing vast transformation to provide its citizen with an efficient, transparent, responsive and connected government. The Malaysian government has introduced the Public-Sector Transformation Framework (PSTF) which aims to make it a high performing, trustworthy, dynamic and citizen centric public service. Nevertheless, the biggest challenge faced by the public sector is the people in the service itself. Public employees are being criticized for lacking the desired efficiency and expected performance. Based on the assumption that employees will perform their best when they are "engaged", this study explores the factors of employee engagement and the European Foundation for Quality Management (EFQM) model for excellence in building a conceptual framework that is conclusive and holistic. Underpinned by the systems theory, this study identifies the factors of leadership, strategy, people, partnerships and resources, processes, products and services, work environment, well-being and work-life balance as the factors that drive engagement towards the realization of citizen centric public service excellence.